Синтез кристаллов кубического нитрида бора в присутствии углеродных материалов – алмаза и графита - Боримский, И.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
It is shown, that introduction of carbon materials - diamond and graphite in a reactionary
charge mixture for cBN synthesis reduces the fractional conversion hBN→сBN and influences a
habitus of formed crystals. It is shown, that crystals of diamond with sizes more than 10 microns
are not the crystallization centers at a cBN synthesis.